Effect of physical training on liver expression of activin A and follistatin in a nonalcoholic fatty liver disease model in rats - Silva,R.N. (2014)
Nonalcoholic fatty liver disease (NAFLD) is characterized by fat accumulation in the liver and is associated with obesity and insulin resistance. Activin A is a member of the transforming growth factor beta (TGF)-β superfamily and inhibits hepatocyte growth. Follistatin antagonizes the biological actions of activin. Exercise is an important therapeutic strategy to reduce the metabolic effects of obesity. We evaluated the pattern of activin A and follistatin liver expression in obese rats subjected to swimming exercise. Control rats (C) and high-fat (HF) diet-fed rats were randomly assigned to a swimming training group (C-Swim and HF-Swim) or a sedentary group (C-Sed and HF-Sed). Activin βA subunit mRNA expression was significantly higher in HF-Swim than in HF-Sed rats. Follistatin mRNA expression was significantly lower in C-Swim and HF-Swim than in either C-Sed or HF-Sed animals. There was no evidence of steatosis or inflammation in C rats. In contrast, in HF animals the severity of steatosis ranged from grade 1 to grade 3. The extent of liver parenchyma damage was less in HF-Swim animals, with the severity of steatosis ranging from grade 0 to grade 1. These data showed that exercise may reduce the deleterious effects of a high-fat diet on the liver, suggesting that the local expression of activin-follistatin may be involved.